Association between neuroticism and physical activity: a systematic review and meta-analysis - Ma, Wenxue; Wang, Xiaotian; Qiu, Wentao; Nie, Yuyang; Gao, Rong; Liu, Cong (Frontiers in Human Neuroscience, 2025)
BackgroundPhysical activity has been shown to be associated with neuroticism, a personality trait reflecting emotional instability and a tendency toward negative emotions. Understanding this relationship is crucial for developing effective mental health interventions. However, the underlying mechanisms and the strength of this association remain insufficiently understood.ObjectiveThis systematic review and meta-analysis aims to examine the current research on the relationship between neuroticism and physical activity, analyze their correlations and moderating factors, and investigate the potential bidirectional mechanisms linking these two factors.MethodsFollowing the PRISMA guidelines, we conducted a comprehensive search of Web of Science, PubMed, ProQuest, Scopus, and EBSCOhost for studies published between January 2000 and November 2024. We included English-language studies across all age groups that employed cross-sectional, longitudinal, or cohort designs. Studies focusing on special populations, non-peer-reviewed works, samples with fewer than 50 participants, non-empirical studies, and reviews were excluded. Data extraction was performed using standardized forms, and a meta-analysis was conducted in Stata 18 to assess heterogeneity and publication bias.ResultsAfter screening, 25 studies were included, comprising 15 Pearson correlation analyses and 12 multiple regression analyses. The meta-analysis revealed a significant negative correlation between physical activity and neuroticism, with an average correlation coefficient r = −0.141. This suggests that higher levels of physical activity are associated with lower levels of neuroticism. Specifically, the average standardized coefficient β for neuroticism inhibiting physical activity was −0.150, indicating that for every one standard deviation increase in neuroticism, physical activity decreases by approximately 0.150 standard deviation units. Conversely, the average standardized coefficient β for physical activity affecting neuroticism was −0.113, suggesting a potential reduction in neuroticism with increased physical activity, although this effect was not statistically significant across the limited number of studies.ConclusionOur findings confirm a significant negative association between physical activity and neuroticism, highlighting the potential of physical activity as a strategy for improving mental health. However, establishing causality requires further verification through longitudinal and experimental designs. The results emphasize the need for personalized interventions targeting individuals with high neuroticism. Future research should prioritize diverse cultural samples, standardized measurement protocols, and mechanistic investigations of this bidirectional relationship to better understand the underlying processes and develop effective interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251051360, identifier: CRD420251051360.